Brain abscess with unusual organism Staphylococcus hemolyticus in a renal transplant recipient - A case report - Neeharika Jonnalagadda; Swarnalatha Guditi; Uttara Das; Raja Karthik Kalidindi; Sarang Vijayan; Ravi Kumar Patel; Ashish Nayak; Gangadhar Taduri (Indian Journal of Transplantation, 2022)
The immunosuppressive medications in renal transplant recipients are associated with increased risk of infections, leading to significant morbidity and mortality. Here, we report a case of focal brain abscess, presented to us, 8 months after deceased donor renal transplantation with headache and altered mentation. Patient had a history of fungal pneumonia 3 months before presenting illness and received intravenous liposomal amphotericin B, for 6 weeks. On evaluation, he was found to have brain abscess, with mild graft dysfunction. Computerized tomography-guided stereotactic aspiration of the brain abscess was done which grew Staphylococcus hemolyticus. Intravenous catheter placed for 6 weeks for antifungal therapy for the management of previous fungal pneumonia was thought to be cause of staphylococcal infection. He was managed with intravenous clindamycin and levofloxacin for 6 weeks as per antibiogram and immunosuppressive medications were reduced. After 6 months of follow-up, patient was asymptomatic with normal renal function and minimal immunosuppressive medications.